Tingkat Kebutuhan Perawatan Periodontal Pada Lansia Di Panti Wredha Dharma Bhakti Surakarta Tahun 2016 - SAZALI, HAN FATHUL IMAM; , drg. Ana Riolina, MPH; , drg. Retno Sari (2016)
Aging is a natural process that occurs in humans. The aging process will cause various problems of physical-biological, psychological and social. Elderly undergo biological aging process is ongoing which is characterized by decreased physical endurance and more vulnerable to diseases including periodontal disease. The purpose of this study to know the level of periodontal treatment needs of the elderly with CPITN index based in nursing homes Wredha Dharma Bhakti Surakarta in 2016. This study is a descriptive research with approach of Cross Sectional Study. This research was conducted in nursing homes Wredha Dharma Bhakti Surakarta with the sample aged> 45 years as many as 84 people. Examination of periodontal status is done by using an index of WHO's Community Periodontal Index of Treatment Needs (CPITN). The results showed that there were not found healthy periodontal and bleeding on probing, 23 people (41.8%) contained sub-supragingival calculus (score 2), 19 (34.5%) have pockets as deep as 3.5-5.5 mm, 13 people (23.6%) own pockets> 6 mm.